The Effects Of Structured Versus Unstructured Online Training Modules On Cyber Security Awareness And Perceived Behaviour Among College Students - Muniandy, Lalitha (2017)
This study investigated the effects of structured versus unstructured online training module on college students’ cyber security awareness and perceived cyber security behaviour. The two modes of online training modules were incorporated with the following cyber security aspects: password usage, phishing, social engineering, online scam and malware. The study was conducted in a well-established university college located in the Northern region of Peninsular Malaysia. A total of 240 respondents from four faculties of the university college participated in the study. A quasi-experimental, post-test design was adopted as a research design for the study. The respondents’ motivation types (intrinsic and extrinsic) as well as specialization areas (technical and non-technical) were manipulated as the moderating factors. Two instruments, Intrinsic and Extrinsic Motivation Scale Questionnaire (IEMSQ) and Cyber Security Behaviour and Awareness Instrument (CSBAI) were used in this study. IEMSQ was used to categorize the respondents according to their motivation types. CSBAI was used to measure the cyber security awareness and perceived cyber security behaviour after the training. The two online training modules were designed using the ADDIE Model, Gagne’s Nine Events of Instruction and Mayer’s Cognitive Theory of Multimedia Learning. The contents of the modules were designed by incorporating Protection Motivation Theory (PMT). In structured online training module, the students were presented with the topics in a linear approach. The students were xxi presented with the learning materials in predetermined sequence. Conversely, in unstructured online training module, the student could choose and learn the sub topics of the main module according to their preference. Six null hypotheses were formulated for this study. Inferential statistical analysis methods, independent groups t-test and two-way ANOVA were used to analyze the data. The results of the study showed that structured online training module is more effective than the unstructured online training module in changing the perceived cyber security behaviour of the respondents. Both modules effectively instilled cyber security awareness among the respondents. The effect of motivation type is limited while specialization area did influence the cyber security awareness of the respondents. The types of online training modules played a more important role than the specialization areas in improving the perceived cyber security behaviour of the respondents. This shows that education and training are important in addressing issues related to cyber security awareness and behaviour of college students.